Translation Techniques of Modality Metaphor in Anne of Green Gables - Yurike Suhertian Poyungi; Mangatur Nababan; Riyadi Santosa (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2021)
This is a descriptive qualitative research that aims to analyze the types of modality metaphor and their translation techniques in the novel entitled Anne of Green Gables. It is a translation research using Systemic Functional Linguistic (SFL) approach. Data were collected by content analysis and focus group discussion (FGD). The data were analyzed by Spradely’s data analysis method. The content analysis is used to analyze the types of modality metaphor based on Halliday and Matthiessen’ theory. Furthermore, the translation technique is analyzed by Molina and Albir’s classification and is done by focus group discussion. The result of this research shows that there are two types of modality metaphor found in the novel, they are probability and obligation. Moreover, the translation techniques that used to translate the modality metaphor are established equivalence, compensation, paraphrase, modulation, deletion, discursive creation and implicitation. The use of these translation techniques shows the translator creativity to translate the modality metaphor.